A comparative effectiveness trial of two faecal immunochemical tests for haemoglobin (FIT). Assessment of test performance and adherence in a single round of a population-based screening programme for colorectal cancer. Issue 3 (14th December 2016) - Passamonti, Basilio; Malaspina, Morena; Fraser, Callum G; Tintori, Beatrice; Carlani, Angela; D'Angelo, Valentina; Galeazzi, Paola; Di Dato, Eugenio; Mariotti, Loretta; Bulletti, Simonetta; D'Amico, Maria Rosaria; Gustinucci, Daniela; et al.
Abstract : Aim: To compare acceptability and diagnostic accuracy of a recently available faecal immunochemical test (FIT) system (HM-JACKarc) with the FIT routinely used in an established screening programme (OC-Sensor). Design: Randomised controlled trial (ISRCTN20086618 ) within a population-based colorectal cancer (CRC) screening programme. Subjects eligible for invitation in the Umbria Region (Italy) programme were randomised (ratio 1:1) to be screened using one of the FIT systems. Results: Screening uptake among the 48 888 invitees was the same for both systems among subjects invited in the first round and higher with OC-Sensor than with HM-JACKarc (relative risk (RR): 1.03; 95% CI 1.02 to 1.04) among those invited in subsequent rounds. Positivity rate (PR) was similar with OC-Sensor (6.5%) as with HM-JACKarc (6.2%) among subjects performing their first FIT screening and higher with OC-Sensor (5.6%, RR: 1.25, 95% CI 1.12 to 1.40) than with HM-JACKarc (4.4%) among those screened in previous rounds. Positive predictive value (PPV) (OC-Sensor: 25.9%, HM-JACKarc: 25.6%) and detection rate (DR) (OC-Sensor: 1.40%; HM-JACKarc: 1.42%) for advanced neoplasia (AN: CRC + advanced adenoma) were similar among subjects performing their first FIT screening. The differences in the AN PPV (OC-Sensor: 20.3%, HM-JACKarc: 22.6%) and DR (OC-Sensor: 0.96%, HM-JACKarc: 0.83%) among those screened in previous rounds were not statistically significant. The number needed to scope to detect one AN was 3.9 (95% CI 5.8 to 2.9) and 3.9 (95% CI 5.5 to 2.9) at first and 4.9 (95% CI 5.8 to 4.2) and 4.4 (95% CI 5.3 to 3.7) at subsequent screening, with OC-Sensor and HM-JACKarc, respectively. Conclusions: Our results suggest that acceptability and diagnostic performance of HM-JACKarc and of OC-Sensor systems are similar in a screening setting. Trial registration number: ISRCTN20086618 ; Results.